Aplicación de un humedal artificial a escala piloto para el tratamiento de aguas residuales domésticas en una planta de beneficio minera - Alvarez Gaona, Helen Nahomy; Valarezo Macas, Maria Jose (Machala : Universidad Técnica de Machala, 2025)
The principal objective of the research is to implement an artificial wetland system for the treatment of domestic wastewater at a mining processing plant. The plant species Phragmites australis was selected. The wetland design is based on mathematical equations that take into account variables such as flow rate, contaminant concentration, reaction constant, and granular medium porosity. To evaluate the efficiency of the system, the wastewater was characterized before treatment, obtaining values of 1550 mg/l of COD, 408 mg/l of BOD5, and 1,600,000 NMP/100 ml of fecal coliforms, exceeding the maximum permissible limits. The results of the experiment showed removal efficiencies of 96%, 97%, and 98% for BOD5, Fecal coliforms and COD, respectively. The percentages indicate acceptable purification capacity; however, the final fecal coliform value (46,000 MPN/100 ml) is not within the range permitted by regulations. Therefore, it is necessary to apply an adequate primary treatment to reduce the concentration of contaminants and ensure the proper functioning of the wetland.
La investigación tiene como objetivo principal implementar un sistema de humedal artificial para el tratamiento de aguas residuales domésticas en una planta de beneficio minera, se seleccionó la especie vegetal Phragmites Australis. El diseño del humedal se fundamenta en ecuaciones matemáticas considerando variables como caudal, concentración del contaminante, constante de reacción y porosidad del medio granular. Para evaluar la eficiencia del sistema, se realizó una caracterización del agua residual previo al tratamiento, obteniendo valores de 1550 mg/l de DQO, 408 mg/l de DBO5 y 1600000 NMP/100ml de Coliformes Fecales sobrepasando los límites máximos permisibles. Los resultados de la experimentación mostraron una eficiencia de remoción de 96%, 97% y 98% en DBO5, Coliformes fecales y DQO, respectivamente. Los porcentajes evidencian una capacidad aceptable de depuración, sin embargo, el valor final de coliformes fecales (46000 NMP/100ml) no se encuentran dentro del rango permitido en la normativa. Por lo cual, es necesario aplicar un tratamiento primario adecuado para disminuir la concentración de los contaminantes para tener un buen desempeño del humedal.
Keywords: HUMEDAL ARTIFICIAL; AGUAS RESIDUALES; DQO; DBO5